Investigation of the presence of salmonella and shigella in artesian well waters used for drinking in bursa - Figen Çetinkaya; Recep Çıbık; Ece Soyutemiz (Eurasian Journal of Veterinary Sciences)
The study was performed to investigate the presence of Salmonella and Shigella species in artesian well water samples collected from several neighbourhoods and villages in Bursa and used as drinking water. For this purpose, a total of 30 water samples were analysed for these pathogens by using the isolation method described by FDA (The US Food and Drug Administration). Neither Salmonella nor Shigella was isolated from any of the analysed samples.